2019
DOI: 10.24815/jimeka.v4i3.12580
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Partisipasi Masyarakat, Kompetensi Sumber Daya Manusia, Dan Pengawasan Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Pada Kabupaten Aceh Barat Daya)

Abstract: The purpose of this study is to examine the effects of community participation, human resource competence, and supervision on accountability of village fund management (a case study in Kabupaten Aceh Barat Daya). This is a quantitative study with questionnaire used as the primary data elicitation and Likert scale as the measure. The study was carried out in Kabupaten Aceh Barat Daya. A total of 120 respondents were selected, consisting of the villages’ tuha peut and public figures. The simple random sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 3 publications
1
8
0
15
Order By: Relevance
“…Other factors which can determine the effectiveness of village fund allocation is supervision. Researched by Umaira and Adnan (2019), Atmadja and Saputra (2018), Munti and Fahlevi (2017) found a positive and significant relation between supervision of accountability in village fund allocation management. Based on the explanation above, the purpose of this research is to examine and analyze whether the competence of village officials, community participation and supervision affect the accountability of village fund allocation management.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other factors which can determine the effectiveness of village fund allocation is supervision. Researched by Umaira and Adnan (2019), Atmadja and Saputra (2018), Munti and Fahlevi (2017) found a positive and significant relation between supervision of accountability in village fund allocation management. Based on the explanation above, the purpose of this research is to examine and analyze whether the competence of village officials, community participation and supervision affect the accountability of village fund allocation management.…”
Section: Introductionmentioning
confidence: 92%
“…Community participation can be one of the factors which determine the effectiveness of village fund management. Research by Naimah (2017), Putra and Rasmini (2019), Umaira and Adnan, (2019) found an effect between community participation toward the accountability of village fund management. Other factors which can determine the effectiveness of village fund allocation is supervision.…”
Section: Introductionmentioning
confidence: 99%
“…Sejalan dengan hasil penelitian Saputra (2018), yang menyatakan bahwa penganggaran partsisipatif berpengaruh terhadap slack anggaran pada SKPK di Pemerintah Aceh. Hal senada juga dinyatakan oleh (Julianto & Dewi, 2019) dan (Umaira & Adnan, 2019) bahwa partisipasi masyarakat bepengaruh scara positif signifikan terhadap pengelolaan dana desa.…”
Section: Pengaruh Tingkat Partisipasi Masyarakat Terhadap Penyerapan Anggaran Dana Desaunclassified
“…Tingkat KAD yang tinggi akan meningkatkan akuntabel pengelolaan ADD, sehingga kompetensi aparatur desa memiliki hubungan dan pengaruh terhadap pengelolaan ADD (Masruhin & Kaukab, 2019). Penelitian mengenai KAD terhadap pengelolaan ADD atau pengelolaan DD sudah pernah dilakukan oleh Mada et al (2017); Umar, Usman, & Purba (2018); Masruhin & Kaukab (2019); Umaira & Adnan (2019); Karim, Lahay, Monoarfa, Adam, & Suardi (2019); (Atiningsih & Ningtyas (2019); Tarjo (2019); Aprilya & Fitria (2020); Yennisa, Wahyuningsih, & Budiarto (2020); Raharja, Suherman, & Alamsyah (2020); Diatmika & Rahayu (2020); Pahlawan, Wijayanti, & Suhendro (2020); (Pratiwi & Dewi (2021); Heldawati (2021); Sari & Padnyawati (2021); Zulkifli, Sandrayati, & Ariani (2021); Hayati & Amalia (2021); Suryandari & Pratama (2021) yang menemukan bahwa KAD mempunyai pengaruh terhadap pengelolaan ADD atau pengelolaan DD baik dari segi akuntabilitas, efektivitas maupun keberhasilan sesuai dengan penelitian yang dikaji peneliti. Oleh sebab itu, maka dapat dibentuk hipotesis sebagai berikut:…”
Section: Hubungan Kad Dengan Pengelolaan Addunclassified